Value Chain and Economic Development: the Case of the Colombian Coffee Industry - Parente-Laverde, Ana-Maria (Organizations and Markets in Emerging Economies, 2020)
Dependency on natural resources has made economies unstable because of the fluctuation of commodity prices. However, coffee production has not had this effect on the Colombian economy owing to the process of upgrading the value chain, with the Colombian National Federation of Coffee Growers taking the lead. Using a case study methodology, the present article aims to analyse how the process of upgrading the value chain in the Colombian coffee industry has contributed to the economic development of the country, represented as an improvement of the country’s infrastructure and living conditions, economic growth, industrialisation level and education access perspectives.
Keywords: Colombia; upgrading value chain; economic development; coffee industry